2022
DOI: 10.3389/fonc.2022.819960
|View full text |Cite
|
Sign up to set email alerts
|

Application Effect of ICG Fluorescence Real-Time Imaging Technology in Laparoscopic Hepatectomy

Abstract: This study aimed to evaluate the efficiency and safety of indocyanine green (ICG) fluorescence real-time imaging-guided technology in laparoscopic hepatectomy. A retrospective analysis of patients with primary liver cancer in the First Affiliated Hospital of USTC from January 2018 to October 2021, including 48 cases of fluorescence-guided laparoscopic hepatectomy (FGLH) and 60 cases of traditional laparoscopic hepatectomy (LH), was conducted. R0 resection rate, operation time, intraoperative blood loss, compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…1 . Conclusively, seven retrospective cohort articles encompassing 598 patients with 327 patients in the non-ICG group, and 271 patients in the ICG group were analyzed [ 25 31 ]. The number of tumors was 728 in total, comprising 364 tumors in the non-ICG group, and 364 tumors in the ICG group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 . Conclusively, seven retrospective cohort articles encompassing 598 patients with 327 patients in the non-ICG group, and 271 patients in the ICG group were analyzed [ 25 31 ]. The number of tumors was 728 in total, comprising 364 tumors in the non-ICG group, and 364 tumors in the ICG group.…”
Section: Resultsmentioning
confidence: 99%
“…In total, seven studies [ 25 31 ] reported the R0 resection rate: 98.6% (359/364) in the ICG group and 93.1% (339/364) in the non-ICG group. Heterogeneity was not observed ( I 2 = 0%, P = 0.56).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 studies ( 22 , 24 , 26 34 ) including 883 patients reported the intraoperative blood loss. there was highly heterogeneity between the two groups ( p < 0.0001, I 2 = 73%), and a random-effects model analysis was used.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, CLI involves some controversial issues of radiation protection and occupation exposure, which limits the popularity of its clinical practice. In contrast, near-infrared fluorescence (NIRF) imaging using indocyanine green (ICG), a fluorescent contrast dye approved by Food and Administration (FDA), has been greatly broadened from ophthalmology ( 11 ), liver surgery ( 12 14 ), sentinel lymph nodes biopsy ( 15 ), and flap transfer ( 16 ) to intraoperative navigation in all sorts of tumor resections. In 2009, Kokudo et al ( 17 ) happened to discover that hepatocellular carcinoma fluoresced strongly when these patients received a routine liver function test by intravenous injection of ICG prior to the surgery, which resulted in a clinical trial to investigate this novel fluorescent imaging techniques.…”
Section: Introductionmentioning
confidence: 99%